Studies on Recovery of Performance of Fouled Nanocomposite Ultrafiltration Membranes on Cleaning after Treatment of Oil–Water Emulsions - A. K. Ghosh; V. S. Mamtani; A. K. Adak (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Herein, we discussed the pure water flux recovery of carbon based nanofillers embedded polyvinyl chloride nanocomposite membranes after physical cleaning through backwashing & flushing with flow reversal and after chemical cleaning using hydrochloric acid and caustic soda. The water flux recovery by backwashing is more than that by forward flushing for all the membrane but it is more effective in carbon black (CB) & graphitized carbon black (GCB) carbon-based membranes than relatively hydrophilic multiwalled carbon-nanotube (MWCNT) & carboxylated multiwalled carbon-nanotube (CMWCNT) based nanocomposite membranes. The highest water flux recovery was found ~96% for nanocomposite membranes by backwashing and caustic soda cleaning. The combination of backwashing and caustic soda cleaning could be the most effective method of cleaning of oil-water fouled membranes to restore the maximum water flux.
Keywords: Membrane; Polyvinyl Chloride; Nanocomposite; Fouling; Oil-Water Separation